PANDANGAN HUKUM PROGRESIF DAN MASLAHAH MURSALAH TERHADAP PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TENTANG PENGUJIAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 - Puji Kurniawan (Yurisprudentia: Jurnal Hukum Ekonomi, 2021)
The presence of progressive law as emancipatory (liberation) on crucial issues in social relations. The problem of social relations in question is a political, economic, and socio-cultural issue. Progressive law is not only seen from the law itself but sees it from the social goals it wants to achieve. This paper looks at the progressive legal values in the Constitutional Court's decision in examining Law No. 1/1974 with the consequences that arise from the operation of the law